Implementation of PRIME-HRM Program Using Cloud-Based Technology - Manahan, Jacob; Lacatan, Luisito Lolong; Miguel , Ana Romina (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This paper exhibits how cloud based technology, with a focus on Human Resource Information System (HRIS), can be used to aid the Department of Health (DOH) implement the Program to Institutionalize Meritocracy and Excellence in Human Resource Management (PRIME-HRM) which has been in effect for government agencies in the Philippine since 2012. The objective of this study is to create a cloud based system of HRIS that could be used to improve the human resource process of the DOH and bring significant change to the traditional process currently used by the department. In order to do this, the agile methodology was used in which the requirements were carefully analyzed, the system was designed according to set criteria, selected the most feasible vendor, releasing the system, and next sprint. The product functions were also determined which are employee management, recruitment management appointment and classification, learning and development, and performance management along with the requirement specifications which are the functional and non-functional. The results of testing determined that the system operating as planned and the algorithms were able to produce the expected results. The research has concluded that it is feasible to create a cloud based HRIS that could help in the implementation of the PRIME-HRM.